(untitled) (Revista de História Regional, 2007)
This work presents some results of a research which intended to follow the changes occurred in the political and economical options adopted by the members of the political elite of Parana State during the 1980 and 1990 decades and what was their position about the neoliberal ideas which had been growing up in Brazil and in the world from the second half of the 70s.